2019
DOI: 10.1002/arch.21592
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of an iron‐binding protein, ferritin heavy chain subunit, from the swallowtail butterfly, Papilio xuthus

Abstract: Ferritin, which is ubiquitous among all living organisms, plays a crucial role in maintaining iron homeostasis, immune response, and detoxification. In the present research, we identified an iron-binding protein, ferritin heavy chain subunit, from Papilio xuthus and named PxFerHCH. The complete complementary DNA of PxFerHCH was 1,252 bp encoding a sequence of 211 amino acids, which includes an iron-responsive element. Phylogenetic analysis showed that PxFerHCH is clustered with Manduca sexta and Galleria mello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…found that the injection of recombinant ferritin helped inhibit bacterial growth in the silkworm Bombyx mori by limiting the iron level in the hemolymph. Similar results have indicated that ferritin expression is upregulated in response to pathogen challenges in the swallowtail butterfly Papilio xuthus (Lepidoptera), 22 the beetle Tribolium castaneum (Coleoptera), 23 the bumblebee Bombus ignitus (Hymenoptera), 24 the horseshoe crab Limulus (Merostomata) 25 and the ark shell Scapharca broughtonii (Lamellibranchia) 26 . Taken together, these findings indicate that ferritin can function as an acute antibiotic protein by storing iron in host cells to inhibit pathogen growth.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…found that the injection of recombinant ferritin helped inhibit bacterial growth in the silkworm Bombyx mori by limiting the iron level in the hemolymph. Similar results have indicated that ferritin expression is upregulated in response to pathogen challenges in the swallowtail butterfly Papilio xuthus (Lepidoptera), 22 the beetle Tribolium castaneum (Coleoptera), 23 the bumblebee Bombus ignitus (Hymenoptera), 24 the horseshoe crab Limulus (Merostomata) 25 and the ark shell Scapharca broughtonii (Lamellibranchia) 26 . Taken together, these findings indicate that ferritin can function as an acute antibiotic protein by storing iron in host cells to inhibit pathogen growth.…”
Section: Introductionsupporting
confidence: 67%
“…It is extensively believed that ferritin is ubiquitously distributed among living organisms and consists of two subunits, Fer1HCH and Fer2LCH, in insects. In this study, NlFer1 and NlFer2 from BPH were found to possess ferritin domains and signal peptides similar to those from other species, 15,22,[45][46][47][48][49] suggesting that they might have similar functions in iron homeostasis. 19,46 However, the tissue expression patterns of ferritin vary slightly among different species.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The relative expression level of ferritin heavy chain subunit from Papilio xuthus sharply increased in response to bacterial (Escherichia coli and Staphylococcus aureus) challenge [27]. The infection rate and proliferation rate of white spot syndrome virus in ferritin-silenced Procambarus clarkii were significantly increased [28].…”
Section: Discussionmentioning
confidence: 99%